Assessment of Urban Disaster Resilience in Dhaka North City Corporation (DNCC), Bangladesh. (2018) - Kabir, Md. Humayun; Sato, Miharu; Habbiba, Umma; Yousuf, Tariq Bin
Abstract: The present study measures the current level of urban disaster resilience of Dhaka North City Corporation (DNCC) by assessing the challenges and potentialities in different aspects of urban system using Urban Disaster Resilience Index (UDRI) model. UDRI was developed based on Climate Disaster Resilience Index (CDRI) introduced by the International Environment and Disaster Management Laboratory of Kyoto University Graduate School of Global Environmental Studies, Japan in 2008. UDRI measures urban disaster resilience by considering five dimensions: physical, social, economic, institutional and natural and shows resilience level in scores from 1-5 where 1 representing very poor and 5 the best. UDRI was calculated for the 36 wards under 5 zones of DNCC. Findings show that the utility services such as electricity, water and drainage system, accessibility to roads, housing and land-use, health facilities, social capital, community knowledge and preparedness about disasters and Disaster Risk Reduction (DRR), and environmental conditions are each playing a role in determining the resilience. From the overall resilience analysis, DNCC's Overall UDRI (all ward average score of the 5 dimensions) scored 2.52, while the physical and social resilience are higher (3.37 and 2.53 respectively) than the other dimensions on average whereas natural and institutional resilience show low scores (2.37 and 2.11 respectively). As compared to an assessment done in 2010 when overall UDRI score of then Dhaka City Corporation (DCC) was 2.35, the city realized a significant improvement in physical and economic resilience, however, scores of social, institutional, and natural resilience dropped. This indicates that holistic and continuous approach is required as risk situation changes constantly and improving infrastructure alone cannot ensure disaster resilience of a city. The analysis suggests that mainstreaming of DRR, allocation of budget for DRR, environmental policy, and community preparedness are key challenges to lead DNCC towards more resilient and safer city.